The The Effect of Motivation, Product Catalog and Installment Payment System on Consumer Buying Interest in Oriflame Products : (Studi pada Santri PPA Latee 1 Guluk-Guluk sumenep Madura) - Fitriyatul Helmiyah; Anna Zakiyah Hastriana (Yayasan Bina Internusa Mabarindo, 2024)
The basis of this study is the condition of very tight and high business competition, especially in the cosmetic industry. Therefore, cosmetic companies need to design marketing strategies and strategies to understand their consumer behavior in order to survive in today's very strong competition. The purpose of this study was to analyze the effect of product catalog motivation and installment payment system on consumer buying interest in Oriflame products, focusing on the Latee 1 Guluk-Guluk student group. This study used a quantitative approach with survey techniques whose sampling used the purposive sample method which produced 100 samples. The number of samples obtained using Purposive Sampling technique is as many as 100 samples. Data were collected through questionnaires and analyzed using multiple linear regression analysis methods and carried out validity tests and classical assumption tests using SPSS 16. The results of the study show that motivation, product catalog, and payment system have a positive influence on consumer buying interest in oriflame products. This research makes an important contribution to Oriflame and its peers in understanding some of the factors that influence consumer buying interest. By understanding the importance of product catalog motivation and installment payment systems, companies can improve their marketing strategies and increase sales of their products. In addition, the study also provides insight to Latee 1 Guluk-Guluk students and other potential consumers on the factors to consider when purchasing Oriflame products.